Central markers of neuroinflammation in alcohol use disorder: A meta‐analysis of neuroimaging, cerebral spinal fluid, and postmortem studies. (28th February 2023) - Adams, Claire; Perry, Nina; Conigrave, James; Hurzeler, Tristan; Stevens, Julia; Yacou Dunbar, Kristiane P.; Sweeney, Alicia; Lee, Kylie; Sutherland, Greg; Haber, Paul; Morley, Kirsten C.
Abstract: Introduction and aims: There is emerging evidence that heavy long‐term alcohol consumption may alter the neuroimmune profile. We conducted a meta‐analysis of the association between alcohol use disorder (AUD) and the extent of neuroinflammation using cerebrospinal (CSF), PET (Positron Emission Tomography), and postmortem studies. Design and methods: A comprehensive search of electronic databases was conducted using the Preferred Reporting Items for Systematic Review and Meta‐Analysis Protocols (PRISMA‐P) for AUD‐related terms in combination with neuroinflammatory markers and cytokine‐ and chemokine‐related terms for CSF, PET, and postmortem studies. Participants had to meet established criteria for AUD and/or heavy alcohol consumption with dependence features and be compared with healthy controls. Papers retrieved were assessed for inclusion criteria and a critical appraisal was completed using the Newcastle‐Ottawa Scale. A meta‐analysis was conducted on postmortem and PET studies. Results: Eleven papers met the inclusion criteria with CSF, PET, and postmortem studies included in the final analysis. Postmortem studies demonstrate significant heterogeneity (𝑄 (14) = 62.02, 𝑝 < 0.001), with the alcohol group showing higher levels of neuroimmune markers than controls (𝑑 = 1.50 [95% CI 0.56, 2.45]). PET studies demonstrated a lower [ 11 C] PBR28 total volume of distribution ( V T ) for translocator protein in the hippocampus ( g  = −1.95 [95% CI −2.72, −1.18], p  < 0.001) of the alcohol group compared to controls. Conclusion: There is emerging evidence across multiple diagnostic modalities that alcohol impacts neuroimmune signaling in the human brain. Abstract : This meta‐analysis of alcohol use disorder and neuroinflammation using cerebrospinal (CSF), PET (Positron Emission Tomography) and post‐mortem studies indicates that there is emerging evidence across multiple diagnostic modalities that alcohol may impact on neuroimmune signalling in the human brain. Targeting the neuroimmune response may be a promising avenue for future treatment research.